Notes on the Metrocoris lituratus group (Heteroptera: Gerridae: Metrocoris) with descriptions of four new species in Sichuan Basin from China - Ye, Zhen; Chen, Ping-Ping; Bu, Wen-Jun (Zootaxa, 2016)
This paper provides the descriptions of four new species from eastern and southern regions of the Sichuan Basin in China: Metrocoris astictus sp. nov. and M. falciformis sp. nov. from Sichuan Province, M. guizhouensis sp. nov. and M. zhengi sp. nov. from Guizhou Province. M. sichuanensis Chen & Nieser, 1993 is currently transferred from the M. stali group to the M. lituratus group. A junior synonym M. bui Chen & Zettel, 1999 is proposed. Photographs of the male and female dorsal habitus and male genitalic structures are provided, accompanied by line drawings of male forelegs, endosomal structures and a distributional map of the newly described species. Finally, a key to the males of the species assigned to M. lituratus group is also provided to assist in identification.